2008
DOI: 10.1099/vir.0.82873-0
|View full text |Cite
|
Sign up to set email alerts
|

Supervirulent pseudorecombination and asymmetric synergism between genomic components of two distinct species of begomovirus associated with severe tomato leaf curl disease in India

Abstract: Isolates of two distinct begomovirus species, the severe strain of the species Tomato leaf curl New Delhi virus (tomato leaf curl New Delhi virus-[India:New Delhi:Severe:1992]; ToLCNDV-[IN:ND:Svr:92], bipartite) and the Varanasi strain of the species Tomato leaf curl Gujarat virus (tomato leaf curl Gujarat virus-[India:Varanasi:2001]; ToLCGV-[IN:Var:01], mono/bipartite) infect tomato (Lycopersicon esculentum) and cause severe yield losses in northern India. This study investigated the infectivity properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 38 publications
0
62
0
1
Order By: Relevance
“…The sequences produced as part of this study are in the shaded square viruses share same vector (whitefly) and thus the chance of the transmission of co-existing viruses increases, as the synergism among the virus species increases the amount of both viruses in the systemically infected leaves. As a result, crops which are infected by more than one virus species or by mixed infection, have a potential source of inoculum for both viruses, and whiteflies (Chakraborty et al, 2008). Our findings here have shown that radish in Oman is such a host that can harbor two viruses and thus can act as a reservoir of viruses.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The sequences produced as part of this study are in the shaded square viruses share same vector (whitefly) and thus the chance of the transmission of co-existing viruses increases, as the synergism among the virus species increases the amount of both viruses in the systemically infected leaves. As a result, crops which are infected by more than one virus species or by mixed infection, have a potential source of inoculum for both viruses, and whiteflies (Chakraborty et al, 2008). Our findings here have shown that radish in Oman is such a host that can harbor two viruses and thus can act as a reservoir of viruses.…”
Section: Discussionmentioning
confidence: 68%
“…A mixed infection potentially leads to geminivirus variability Zhou et al, 1997;Fondong et al, 2000). Mixed infections also can affect symptoms, and virus accumulation, because they often result in synergistic interactions (Chakraborty et al, 2008;Alves-Júnior et al, 2009). The mechanism of the synergistic interaction of geminiviruses is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different viruses infecting tomato, leaf curl causing geminiviruses and Cucumber mosaic virus (CMV) are the two major viruses imposing significant threat to successful cultivation of this crop worldwide. During mixed infections, the synergism might result in the exacerbation of disease symptoms, the increase of virus titer, and the complementation of movement defects due to host restrictions, so that either of them can spread systemically and accumulate at higher level (García-Cano et al 2006;Chakraborty et al 2008;Rentería-Canett et al 2011). Geminiviruses are ssDNA viruses causing leaf curl disease in several crop plants including chilli, okra, cotton, cassava, radish, cabbage etc.…”
Section: Introductionmentioning
confidence: 99%
“…Geminiviruses are ssDNA viruses causing leaf curl disease in several crop plants including chilli, okra, cotton, cassava, radish, cabbage etc. (Moffat 1999;Boulton 2003;Mansoor et al 2006;Chakraborty et al 2008;Singh et al 2012). During the last decade, geminiviruses have emerged as the most notorious plant pathogens causing severe crop loss worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed infections are common in the field, favoring recombination and pseudorecombination and facilitating the emergence of new strains or species better adapted to new hosts (Chakraborty et al 2008;Davino et al 2009;Patil & Fauquet 2009;Pita et al 2001).…”
mentioning
confidence: 99%